POTENSI BIVALVIA SEBAGAI BIOINDIKATOR PENCEMARAN LOGAM DI WILAYAH PESISIR - Triyoni Purbonegoro (Pusat Penelitian Oseanografi LIPI, 2018)
POTENTIAL OF BIVALVE AS BIOINDICATOR OF METAL POLLUTION IN THE COASTAL AREA. Bioaccumulation database using various species of marine bivalves is useful to determine which species are suitable as bioindicators in pollution monitoring. In general, metal bioaccumulation in bivalve varies in every location and influenced by the biokinetics of each species depending on the environmental condition. Increasing accumulation of one metal will enhance the accumulation of other metal in bivalve tissue. This needs to be taken into account in interpreting metal concentrations in bivalve. Oysters and mussels have the potential as bio-indicators of metals, especially Cu and Zn, while scallops are more potential as bioindicators of Cd and Zn. Meanwhile, clams has the potential as a bioindicators of Zn. Change in shape (malformation) of bivalve shells due to heavy metal accumulation also observed. The rough structure, attachment of minerals to the shell, and thickening of the shell layer are some forms of changes in bivalve shell morphology.